On a Validity Criterion for the Born Approximation - L. B. Hovakimian
In this presentation a validity criterion for the Born approximation is examined for elastic scattering on a finite range radially symmetric potential in multidimensional space. Our analysis utilizes the transformation properties of the radial Schrödinger equation for S waves. The analytic structure of criterion is found to yield the corresponding results for low dimensional cases in a rather natural way. Some peculiarities of perturbative scattering in 2+Ω dimensions are brought out.
Keywords: Physics; Quantum mechanics, field theories, and special relativity